Umbilical endometriosis: case report and literature review - Camargo, Beatriz Milene de Oliveira; Ziliani, Maria Júlia Da Gama Fortunato; Fortes, Isadora Dufrayer Fânzeres Monteiro; Fortunato, Luiza de Oliveira; Guimarães, Natália Dier; Calais, Rafaela De; Fortunato, Giovana Da Gama (Revista de Medicina, 2023)
Endometriosis is a disease characterized by the presence of endometrial tissue outside the uterine cavity. Umbilical endometriosis consists in the presence of endometrial glands and/or stroma in the inner region of the navel. The objective of this study is to report a secondary umbilical endometriosis case related to previous rectosigmoidectomy and perform a literature review. The pathogenesis of umbilical endometriosis is not yet fully understood, but there are theories attributed to retrograde menstrual flow, metaplastic transformation, and iatrogenic deposition in remnant surgical procedures. The classification into primary or secondary occurs according to the origin of the disease. Symptoms include cyclic abdominal pain and umbilical bleeding. The diagnosis is made by anamnesis and physical examination, being confirmed by complementary exams, such as histopathological analysis. The treatment of choice should be total excision of the lesion and pathological analysis. Hormonal treatments can help in the surgical treatment, regression of the lesion, and prevention of recurrence.